Modified silicone rubbers for fabrication and contacting of flexible suspended membranes of n-/p-GaP nanowires with single-walled carbon nanotube transparent contact. (December 2020) - Kochetkov, F M; Neplokh, V V; Fedorov, V V; Bolshakov, A D; Cirlin, G E; Islamova, R M; Mukhin, I S
Abstract: This work proposes new chemical and mechanical materials and techniques for III-V semiconductor NW/silicone membrane formation and optoelectronic device fabrication. Molecular beam epitaxy (MBE)-synthesized n-, p- and i-GaP NWs were encapsulated by introduced G-coating method into synthesized polydimethylsiloxane- graft -polystyrene and released from the Si growth substrate. The fabricated membranes were contacted with different materials including single-walled carbon nanotubes or ferrocenyl-containing polymethylhydrosiloxane with and without multi-walled carbon nanotubes doping. The electrical connection of the fabricated membranes was verified by electron beam induced current (EBIC) spectroscopy. The developed methods and materials can be applied for fabrication of high quality flexible inorganic optoelectronic devices.